Ionizing Waves in Surface Dielectric Barrier Discharges Plasma Actuators - Ruggero Barni; Hector Eduardo Roman; Claudia Riccardi (Actuators, 2024)
Plasma actuators have been proposed as a tool to produce hydrodynamical effects in the boundary layer of aerodynamical flows. We have analyzed some properties of these systems using suitable plasma diagnostics based on the emissivity characteristics of such plasmas. The direction and the velocity of propagation of the ionizing wave spreading on the dielectric surface were measured (in the 100–200 km/s range), and it was demonstrated that it behaves like a cathode-directed streamer. The averaged electron temperature (4–5 eV) and the reduced field strength (E/N ≈ 6 × 1019 V·m2) of the ionizing wave switching the discharges on were measured, too.